2019
DOI: 10.1002/adtp.201900036
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Microneedle Arrays: Versatile Tools for an Innovative Approach to Drug Administration

Abstract: Mainly designed and realized as a painless alternative to the hypodermic syringe, microneedle-based devices are currently approaching commercial market placement. The considerable academic and industrial investment in this technology is reflected by a multitude of papers published and patents registered every year, which is also a sign of a field in full fermentation. New materials and innovative methodologies are continuously exploited in search of the best performance at the lowest cost. For these reasons, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…The rigid but brittle properties of these materials have been likened to sea urchin thorns made of mineral calcite. As accidents and issues in the administration of the MNs are inescapable, the best materials for MNs should be biodegradable and biocompatible, to avoid complications that occur from accidents such as when the MN tip breaks inside the first few layers of the skin ( Dardano et al, 2019b ).…”
Section: Transdermal Drug Delivery (Tdd)mentioning
confidence: 99%
See 2 more Smart Citations
“…The rigid but brittle properties of these materials have been likened to sea urchin thorns made of mineral calcite. As accidents and issues in the administration of the MNs are inescapable, the best materials for MNs should be biodegradable and biocompatible, to avoid complications that occur from accidents such as when the MN tip breaks inside the first few layers of the skin ( Dardano et al, 2019b ).…”
Section: Transdermal Drug Delivery (Tdd)mentioning
confidence: 99%
“…Developments in the field are saturated, as evidenced by the increased number of academic publications and patents on MNs annually. Continuous efforts to transfer scientific research into the clinical application has been ongoing for the past 20 years, with research groups now taking initial commercializing steps ( Dardano et al, 2019a ). This jump from experimental research to an initial commercialization stage is evidenced in the number of concluded clinical trials in the USA, as can be accessed via https://clinicaltrials.gov/ .…”
Section: Scale-up and Manufacturing Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For CURATE.AI to be implemented in the clinical setting and practice, regulatory standards and qualifications must be satisfied similar to those applied to traditionally defined drugs and devices, with recent additions such as combina tion products [95][96][97] and now medical software. [98][99][100] To address the newly emergent field of medical software, the International Medical Device Regulatory Forum (IMDRF) and Food and Drug Administration (FDA) have broadly classified such software as Software as Medical Device (SaMD) and Clinical Decision Support Software (CDSS).…”
Section: Clinical Implementationmentioning
confidence: 99%
“…However, injection with hypodermic needles are often associated with poor patient compliance and needle phobia. [ 1,2 ] Microneedle patches are alternative portable medical delivery devices that can perforate the stratum corneum and deliver their loaded therapeutic cargoes into the dermis. Such a strategy avoids stimulation of nociceptive nerve endings and minimizes a patient's pain experience.…”
Section: Introductionmentioning
confidence: 99%